Advanced cervical dilatation as a predictor for low emergency cesarean delivery: a comparison between migrant and non-migrant Primiparae - secondary analysis in Berlin, Germany - Jürgen Breckenkamp; Eileen Marie Läcke; Wolfgang Henrich; Theda Borde; Silke Brenne; Matthias David; Oliver Razum (BMC, 2019)
Abstract Background Cesarean rates are higher in women admitted to labor ward during early stages rather than at later stages of labor. In a study in Germany, crude cesarean rates among Turkish and Lebanese immigrant women were low compared to non-immigrant women. We evaluated whether these immigrant women were admitted during later stages of labor, and if so, whether this explains their lower cesarean rates. Methods We enrolled 1413 nulliparous women with vertex pregnancies, singleton birth, and 37+ week of gestation, excluding elective cesarean deliveries, in three Berlin obstetric hospitals. We applied binary logistic regression to adjust for social and obstetric factors; and standardized coefficients to rank predictors derived from the regression model. Results At the time of admission to labor ward, a smaller proportion of Turkish migrant women was in the active phase of labor (cervical dilation: 4+ cm), compared to women of Lebanese origin and non-immigrant women. Rates of cesarean deliveries were lower in women of Turkish and Lebanese origin (15.8 and 13.9%) than in non-immigrant women (23.9%). In the logistic regression analysis, more advanced cervical dilatation was inversely associated with the outcome cesarean delivery (OR: 0.76, 95%CI: 0.70-0.82). In addition, higher maternal age (OR: 1.06, 95%CI: 1.04-1.09), application of oxytocic agents (OR: 0.55, 95%CI: 0.42-0.72), and obesity (OR: 2.25, 95%CI: 1.51-3.34) were associated with the outcome. Ranking of predictors indicate that cervical dilatation is the most relevant predictor derived from the regression model. Conclusions Advanced cervical dilatation at the time of admission to labor ward does not explain lower emergency cesarean delivery rates in Turkish and Lebanese migrant women, despite the fact that this is the strongest among the predictors for emergency cesarean delivery identified in this study.